Abandoned housing projects in Malaysia: A planning law perspective - Md Dahlan, Nuarrual Hilal; Nafees, Seeni Mohamed; Masum, Ahmad; Kyaw, Hla Win (2015)
Housing is a burgeoning industry in Malaysia. Initially housing was provided by the Malaysian Federal Government in the early days of its independence.Later, the private sector was invited by the government to participate in providing housing accommodation to meet the public upsurges in demand for housing.To govern the housing industry spearheaded by the private sector, the Malaysian Government introduced laws. One of the laws is the Town and Country Planning Act 1976 (Act 172) ('TPCA').Nevertheless, despite there are many housing policies and legal means to ensure housing success, there are still issues plaguing housing industry in Malaysia. For an instance one of the big issues is the issue of abandoned housing projects.This issue has been existed since 1970s.Until now, this issue has not been fully addressed and resolved by the government.Many purchasers have become victims in abandoned housing projects, suffered irreparable damage and exorbitant losses.